Comparative Clinical Effectiveness of Population‐Based Atrial Fibrillation Screening Using Contemporary Modalities: A Decision‐Analytic Model - Shaan Khurshid (Wiley, 2021)
Background Atrial fibrillation (AF) screening is endorsed by certain guidelines for individuals aged ≥65 years. Yet many AF screening strategies exist, including the use of wrist‐worn wearable devices, and their comparative effectiveness is not well‐understood. Methods and Results We developed a decision‐analytic model simulating 50 million individuals with an age, sex, and comorbidity profile matching the United States population aged ≥65 years (ie, with a guideline‐based AF screening indication). We modeled no screening, in addition to 45 distinct AF screening strategies (comprising different modalities and screening intervals), each initiated at a clinical encounter. The primary effectiveness measure was quality‐adjusted life‐years, with incident stroke and major bleeding as secondary measures. We defined continuous or nearly continuous modalities as those capable of monitoring beyond a single time‐point (eg, patch monitor), and discrete modalities as those capable of only instantaneous AF detection (eg, 12‐lead ECG). In total, 10 AF screening strategies were effective compared with no screening (300–1500 quality‐adjusted life‐years gained/100 000 individuals screened). Nine (90%) effective strategies involved use of a continuous or nearly continuous modality such as patch monitor or wrist‐worn wearable device, whereas 1 (10%) relied on discrete modalities alone. Effective strategies reduced stroke incidence (number needed to screen to prevent a stroke: 3087–4445) but increased major bleeding (number needed to screen to cause a major bleed: 1815–4049) and intracranial hemorrhage (number needed to screen to cause intracranial hemorrhage: 7693–16 950). The test specificity was a highly influential model parameter on screening effectiveness. Conclusions When modeled from a clinician‐directed perspective, the comparative effectiveness of population‐based AF screening varies substantially upon the specific strategy used. Future screening interventions and guidelines should consider the relative effectiveness of specific AF screening strategies.